Fabrica and three short pieces for chorus and chamber ensemble - Talaroc, Jem Robert Bautista
It is a unique experience writing music with prior knowledge of the stark differences between the surfaces of both popular culture and elitist modern art. The composing of these four graduate pieces marks an important phase in my young composing endeavors, for they explore the inevitable merging between the popular culture in which I grew up, and the modern-classical aesthetics I've acquired in the university. In Fabrica for instance, once may notice the complexity of the sonority of Jose Maceda's music, and yet still finds rhythm as a recognizable element and driving force, as one finds in rock or dance music. The same thing can be said of the three other pieces Salmo, The Rage, and six infinities. But the apparent dichotomy of high and low art evident in my works are merely superficial, for it is my goal, ultimately, to achieve in the music a reconciliation in the dichotomy of which I speak. And to provide context and "humanity" to the wide range of modern sound palettes which the masters of the previous generation have left for us. This will be, I hope, the inception of my humble contribution to the already diversifying world of 21st century music.